TARKIBIDA AZOT, KISLOROD, OLTINGUGURT SAQLAGAN GETEROHALQALI BIRIKMALAR ASOSIDA DIZEL YOQILG‘ILARI XOSSALARINI YAXSHILOVCHI PRISADKALARNI OLISH VA ULARNI XOSSALARINI O‘RGANISH - Babaev , O; Fozilov , F; Mustafoev , M (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
This article presents the synthesis of nitrogen-, oxygen-, halogen- and sulfur-containing heterocyclic compounds, in particular esters of 2-mercaptobenzoxazole, and the results of studying their properties of diesel fuels